HIV/AIDS awareness advertising: representation of the linguistic and socio-cultural repertoires on ZBC/ TV - Mpofu, Phillip (World Academy of Science, Engineering and Technology, 2016)
This paper analyses HIV/AIDS advertisements in the electronic form focusing in particular on the manipulation of the linguistic and socio-cultural repertoire of the target audience in sense creation as part of HIV/AIDS awareness campaigns. By utilizing the communication and discourse analysis models as the methodological tools, this paper analyses the ambiguities and accuracies in the advertisements focusing on language use, socio-cultural references and the reception of the advertisements. This study is based on selected advertisements screened on the Zimbabwe Broadcasting Corporation Television (herein referred in this paper as ZBC TV) in the first half of the year 2009. The paper argues that though the advertisers carefully manipulated the linguistic and socio-cultural repertoire of the recipient audience, inadequacies, ambiguities and assumptions were also detected in the advertisements thereby reducing their effectiveness in their intended purpose.